Helicobacter pylori resistance to antibiotics in Europe and its relationship to antibiotic consumption. Issue 1 (12th May 2012) - Megraud, Francis; Coenen, Samuel; Versporten, Ann; Kist, Manfred; Lopez-Brea, Manuel; Hirschl, Alexander M; Andersen, Leif P; Goossens, Herman; Glupczynski, Youri; ,
Abstract : Objective: Resistance to antibiotics is the major cause of treatment failure of Helicobacter pylori infection. A study was conducted to assess prospectively the antibacterial resistance rates of H pylori in Europe and to study the link between outpatient antibiotic use and resistance levels in different countries. Design: Primary antibiotic resistance rates of H pylori were determined from April 2008 to June 2009 in 18 European countries. Data on yearly and cumulative use over several years of systemic antibacterial agents in ambulatory care for the period 2001–8 were expressed in Defined Daily Doses (DDD) per 1000 inhabitants per day. The fit of models and the degree of ecological association between antibiotic use and resistance data were assessed using generalised linear mixed models. Results: Of 2204 patients included, H pylori resistance rates for adults were 17.5% for clarithromycin, 14.1% for levofloxacin and 34.9% for metronidazole, and were significantly higher for clarithromycin and levofloxacin in Western/Central and Southern Europe (>20%) than in Northern European countries (<10%). Model fit improved for each additional year of antibiotic use accumulated, but the best fit was obtained for 2005. A significant association was found between outpatient quinolone use and the proportion of levofloxacin resistance (p=0.0013) and between the use of long-acting macrolides only and clarithromycin resistance (p=0.036). Conclusion: In many countries the high rate of clarithromycin resistance no longer allows its empirical use in standard anti- H pylori regimens. The knowledge of outpatient antibiotic consumption may provide a simple tool to predict the susceptibility of H pylori to quinolones and to macrolides and to adapt the treatment strategies.